Rheological Behavior, Antimicrobial and Quorum Sensig Inhibition Study of an Argentinean Oregano Essential Oil Nanoemulsion - Asensio, Claudia Mariana; Quiroga, Patricia Raquel; Al-Gburi, Ammar; Huang, Quingron; Grosso, Nelson Rubén (Frontiers in Nutrition, 2020)
In this study, Argentinean OEO NEs were developed. Four NE were prepared: a control (CNE), EONE1 (10.6 mg EO/ g NE), EONE2 (106 mg EO/ g NE), and EONE3 (160 mg EO/g NE) and tested for antimicrobial activity against Staphylococcus aureus ATCC 13565, Listeria monocytogenes Scott A, Pseudomonas aeruginosa ATCC 14213, Escherichia coli O157:H7 using a broth microdilution assay; quorum sensing inhibition in a model using Chromobacterium violaceum ATCC 12472, where the production of violacein was quantified. The chemical composition of the EO was determined by GC-MS. The average particle size (nm) and polydispersity index (PDI) were monitored over 14 days at two different storage temperatures (4 °C and 23 °C). A rheological behavior study was carried out using a dynamic shear rheometer, and flow curves as well as viscoelastic properties were determined. E. coli and L. monocytogenes were the most sensitive microorganisms to EONE (minimum inhibitory concentration [MIC] of 2 mg/mL and 5 mg/mL for EOEN3). Sub-MICs for NE were found at lower concentrations than for pure EO. A significant reduction in violet pigment intensity and colorless coloration (p < 0.05) were observed at different NE concentrations respect to the control sample. The flow behavior index (n) decreased, and the consistency index (k) increased, when the EO concentration was increased. CNE, EONE1, and EONE2 showed liquid-like behavior (G’ < G”) in the low-frequency region, whereas a solid-like behavior (G’ > G”) was observed in the high-frequency region, presenting a viscoelastic behavior, appearing as a wormlike micellar solution. For EONE3, a strong increase in both moduli was observed with increasing OEO concentration. The G’ was about one order of magnitude higher than the G” over the whole frequency range, indicating the presence of a gel-like structure. The incorporation of EOs into an NE increased their stability, lowering the particle size, leading to a wormlike micelle with higher viscosity. Moreover, this NE had good antimicrobial activity and novel quorum-sensing inhibition activity. The results of this study indicated that Argentinean OEO NE can be use into a food system as a natural and stable antimicrobial agent.